(untitled) (Bangladesh Journal of Medical Science, 2021)
Objective: This study aims to prove the effect of supplementation of bitter melon leaves extract on glycemic status in diabetic foot ulcer (DFU). Materials and Methods: This study used a randomized, double-blinded, and placebo-controlled trial. Thirty DFU patients based on PEDIS 1-8 scores who met the criteria were divided into 2 groups consisting of 15 patients as a treatment group with the administration of bitter melon leaves extract at a dose of 6 g/day and 15 patients as a control group of with placebo. This intervention was conducted in 4 weeks. Glycemic status was measured by the value of glycated albumin and examined at baseline and at the end of treatment. Data were analyzed using paired t-test and independent t-test. Results: After 4 weeks of treatment, there was an increase in the baseline value of glycated albumin in the treatment group from 24.5 ± 11.7% to 25.8 ± 12.7% or an increase of 1.3 ± 6.3% and a decrease in the control group from 27.5 ± 13.1% to 25.8 ± 8.5% or a decrease of 1.7 ± 12.4%. The results of the analysis of the effect of supplementation of bitter melon leaves extract on the value of glycated albumin were not significant (p = 0.99). Conclusion: The supplementation of bitter melon leaf extract with a dose of 6 g / day did not significantly affect the value of glycated albumin. Bangladesh Journal of Medical Science Vol.20(2) 2021 p.281-287